Anode mixture for secondary battery, anode including the anode mixture, and secondary battery

By using hydrophobically modified alkali-soluble emulsion and AAM/AA/AN copolymer as the binder composition in the secondary battery anode mixture, the problem of degradation of the stability of the anode mixture is solved, and high initial adhesion and low Resistance extends the life of the secondary battery.

CN114667617BActive Publication Date: 2025-01-17LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180006369.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-21
Filing Date
2021-10-22
Publication Date
2025-01-17
Estimated Expiration
2041-10-22

AI Technical Summary

Technical Problem

In the process of increasing the content of the anode active material of the secondary battery to improve capacity and efficiency, the stability of the anode mixture decreases, resulting in problems of desorption and contamination of the rolls in subsequent processes.

Method used

The hydrophobically modified alkali-soluble emulsion (HASE) and acrylamide (AAM)-based, acrylic acid (AA)-based, acrylonitrile (AN)-based copolymers are used as binder compositions to control their in the anode mixture. The content is between 3 to 10% by weight to achieve the dual function of the adhesive and the thickener, and improve the initial adhesion and stability of the anode.

Benefits of technology

Through the adhesive composition within a specific content range, the high initial adhesion of the anode is ensured, the desorption area during the anode is cut, the initial resistance of the anode is reduced, and the life of the secondary battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005059693080000011
    Figure FDA0005059693080000011
  • Figure FDA0005059693080000021
    Figure FDA0005059693080000021
  • Figure FDA0005059693080000041
    Figure FDA0005059693080000041
Patent Text Reader

Abstract

The present disclosure relates to an anode mixture for a secondary battery, an anode comprising the anode mixture, and a secondary battery. Specifically, in one embodiment of the present disclosure, an anode mixture for a secondary battery comprising a binder composition within a specific content range is provided, wherein the binder composition is a mixture of an AAM / AA / AN copolymer and HASE.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2020-0138514 filed on October 23, 2020, and Application No. 10-2021-0141343 filed on October 21, 2021, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present disclosure relates to an anode mixture for a secondary battery, an anode including the anode mixture, and a secondary battery. Background Art

[0004] As the application of secondary batteries, which have been limited to small electronic devices, expands to various fields such as automobiles, power storage, and the like, various efforts have been made to improve the performance of secondary batteries.

[0005] As an example, a method of improving the capacity and efficiency of a secondary battery by using an anode having a high anode active material content has been proposed. However, as the content of the anode active material increases, the slurry phase of the anode mixture may become unstable and defects may occur in subsequent processes.

[0006] Conventionally, an anode mixture in a slurry phase is prepared by mixing an anode active material and an anode binder in a solvent. At this time, styrene butadiene latex (SBL) is used as an anode binder, and sodium carboxymethyl cellulose (CMC) serving as a dispersant and thickener is added to adjust the viscosity of the anode mixture.

[0007] In this case, SBL has low adhesiveness and CMC is brittle, thus requiring sufficient inclusion of SBL and CMC in the anode mixture. However, when the content of the anode active material is increased for high capacity and high efficiency of the secondary battery, it is inevitable to reduce the content of SBL and CMC.

[0008] As the content of anode active material in the anode mix increases and the contents of SBL and CMC decrease, the slurry phase of the anode mix may become unstable, thereby causing desorption of the anode active material and contamination of rollers in subsequent processes (e.g., a process of applying and drying the anode mix on an anode current collector followed by rolling).

[0009] Therefore, in order to ensure the stability of the slurry phase of the anode mixture and reduce defects in subsequent processes, it is necessary to study an anode mixture whose composition is different from the conventional composition. Summary of the invention

[0010] Technical issues

[0011] In the present disclosure, provided are an anode mixture to which a binder composition having a new composition is applied instead of SBL and CMC, a method of preparing the anode mixture, and an anode and a secondary battery including the anode mixture.

[0012] In the present disclosure, an anode for a secondary battery and a secondary battery including the anode mixture are also provided.

[0013] Technical Solution

[0014] Specifically, in one embodiment of the present disclosure, an anode mixture for a secondary battery is provided, comprising an anode active material and a binder composition.

[0015] Wherein, the adhesive composition comprises:

[0016] Hydrophobically modified alkali soluble emulsion (HASE); and

[0017] A copolymer comprising a first repeating unit derived from an acrylamide (AAM)-based first monomer, a second repeating unit derived from an acrylic acid (AA)-based second monomer, and a third repeating unit derived from an acrylonitrile (AN)-based third monomer, and

[0018] The binder composition may be included in an amount of 3 to 10 wt % based on 100 wt % of the total solid content in the anode mixture.

[0019] In another embodiment of the present disclosure, there is provided a method for preparing an anode mixture for a secondary battery, comprising the following steps:

[0020] preparing a copolymer by polymerizing an acrylamide (AAM)-based first monomer, an acrylic acid (AA)-based second monomer, and an acrylonitrile (AN)-based third monomer;

[0021] preparing an adhesive composition by mixing the copolymer with a hydrophobically modified alkali soluble emulsion (HASE); and

[0022] obtaining an anode mixture by mixing the binder composition with an anode active material,

[0023] Wherein, when the binder composition is mixed with the anode active material, the content of the binder composition is controlled to be 3 to 10 wt % based on 100 wt % of the total solid content in the anode mixture.

[0024] In another embodiment of the present disclosure, there is also provided an anode for a secondary battery, comprising: an anode current collector; and

[0025] An anode mixture layer is located on one side or both sides of the anode current collector and includes the anode mixture.

[0026] In another embodiment of the present disclosure, there is also provided an anode for a secondary battery, comprising: an anode active material; and

[0027] An adhesive comprising a polymer from a hydrophobically modified alkali soluble emulsion (HASE); and a copolymer comprising a first repeating unit from an acrylamide (AAM)-based first monomer, a second repeating unit from an acrylic acid (AA)-based second monomer, and a third repeating unit from an acrylonitrile (AN)-based third monomer,

[0028] The weight ratio between the polymer from the hydrophobically modified alkali soluble emulsion (HASE) and the copolymer is 1:1 to 10.

[0029] In another embodiment of the present disclosure, a secondary battery is provided, including: the above-mentioned anode; an electrolyte; and a cathode.

[0030] Beneficial Effects

[0031] The anode mixture for a secondary battery of the embodiment includes a binder composition that is a mixture of HASE and an AAM / AA / AN copolymer within a specific solid content range, thereby achieving dual functions of a binder and a thickener by one binder composition.

[0032] In particular, an anode mixture including the binder composition in a specific content range can ensure high initial adhesion of the anode, reduce a desorption area during anode slitting, lower initial resistance of the anode, and thereby ultimately improve the life of a secondary battery.

[0033] Therefore, an anode mixture including the binder composition in a specific content range may replace an anode mixture including SBL and CMC. DETAILED DESCRIPTION

[0034] In the present disclosure, the terms “first”, “second”, etc. are used to describe a plurality of components, and these terms are only used to distinguish a certain component from other components.

[0035] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to limit the present invention. Singular forms are intended to also include plural forms, unless the context clearly states otherwise. It is further understood that the terms "comprise", "have" or "have" when used in the present disclosure indicate the presence of the features, numbers, steps, components or combinations thereof, without excluding the presence or addition of one or more other features, numbers, steps, components or combinations thereof.

[0036] In addition, as used herein, when it is mentioned that a layer or element is formed “on” or “over” multiple layers or elements, the layer or element may be formed directly on the multiple layers or elements, or other layers or elements may be additionally formed between multiple layers, on an object, or on a substrate.

[0037] Since the present invention can be modified in various ways and has various forms, its specific embodiments are shown and described in detail in the form of examples. However, it is not intended to limit the present invention to the specific forms disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutes within the scope of the present invention's ideas and techniques.

[0038] In the present disclosure, weight average molecular weight refers to the weight average molecular weight measured by GPC method and calibrated with polystyrene. In the process of measuring the weight average molecular weight calibrated with polystyrene by GPC method, known analyzers, detectors such as refractive index detectors and analytical columns can be used. Conventional temperature conditions, solvents and flow rates can be applied. Specifically, Waters PL-GPC220 and Polymer Laboratories PLgel MIX-B 300 mm length columns can be used for measurement. The evaluation temperature is 160 ° C, 1,2,4-trichlorobenzene is used for solvent, and the flow rate is 1 ml / min flow rate. The sample with a concentration of 10 mg / 10 ml is supplied in an amount of 200 microliters. Mw can be obtained using a calibration curve formed with polystyrene standards. Nine polystyrene standards were used with molecular weights (g / mol) of 2,000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000.

[0039] Anode mixture for secondary batteries

[0040] In one embodiment of the present disclosure, an anode mix including an anode active material and a binder composition may be provided.

[0041] The adhesive composition may include a hydrophobically modified alkali-soluble emulsion (HASE); and a copolymer comprising a first repeating unit derived from an acrylamide (AAM)-based first monomer, a second repeating unit derived from an acrylic acid (AA)-based second monomer, and a third repeating unit derived from an acrylonitrile (AN)-based third monomer (hereinafter, the above copolymer is referred to as "AAM / AA / AN copolymer" in some cases).

[0042] In addition, the content of the binder composition may be limited to a specific range of 3 to 10 wt % or 4 to 10 wt % in the total solid content (100 wt %) in the anode mixture.

[0043] The hydrophobically modified alkali soluble emulsion (HASE) may be a copolymer containing a cationic group, a hydrophobic group, and a nonionic group, which is insoluble in water and exists in the form of latex.

[0044] Latex-type HASE can have a high viscosity (300 to 5000 cP @ 20°C), making it useful for increasing the viscosity of aqueous solutions.

[0045] Meanwhile, in the above copolymer, each repeating unit may be derived from one monomer. For example, the first repeating unit may correspond to a structural unit formed from the first monomer.

[0046] The first monomer may be acrylamide (AAM), the second monomer may be acrylic acid (AA), and the third monomer may be acrylonitrile (AN).

[0047] In the AAM / AA / AN copolymer, the AAM-based first repeating unit can improve the life of the secondary battery due to its high Tg; the AA-based second repeating unit can improve the adhesion of the electrode due to its hydrophilicity; and the AN-based third repeating unit can improve the chemical resistance of the electrolyte due to its hydrophobicity and can improve the life of the secondary battery.

[0048] The adhesive composition including HASE and AAM / AA / AN copolymer can realize the two functions of adhesive and thickener by one adhesive composition. In this sense, the adhesive composition can be referred to as "a single-component adhesive that realizes the functions of adhesive and thickener by one adhesive composition", and can be abbreviated as "single-component adhesive".

[0049] In other words, in the present disclosure, the anode active material, the hydrophobically modified alkali soluble emulsion (HASE) and the binder may not be separately mixed and used, but a single-component binder obtained by pre-mixing the hydrophobically modified alkali soluble emulsion (HASE) and the AAM / AA / AN copolymer containing three specific repeating units may be used and mixed with the anode active material.

[0050] Furthermore, the adhesive according to the present disclosure may use an AAM / AA / AN copolymer instead of a conventional adhesive.

[0051] In addition, according to the present disclosure, when using a one-component adhesive composition comprising a hydrophobically modified alkali-soluble emulsion (HASE) and an AAM / AA / AN copolymer, its solid content range can be within a specific content range, thereby optimally improving the properties of the anode mixture. Thus, using the anode mixture according to the present disclosure can obtain high initial adhesion of the anode, reduce the desorption area during anode cutting, reduce the initial resistance of the anode, and ultimately improve the life of the secondary battery.

[0052] When any one of HASE and AAM / AA / AN copolymer is excluded from the binder composition, the functions of the materials may not be coordinated with each other, thereby reducing the initial adhesion of the anode, the desorption area during anode slicing, the initial resistance of the anode, and ultimately reducing the life of the secondary battery.

[0053] In particular, the binder composition anode mixture included in a specific content range can ensure high initial adhesion of the anode, reduce the desorption area when the anode is cut, lower the initial resistance of the anode, and thus ultimately improve the life of the secondary battery.

[0054] Thus, an anode mixture including the binder composition in a specific content range may replace an anode mixture including SBL and CMC.

[0055] Hereinafter, the anode mixture of this embodiment will be described in more detail.

[0056] Content of adhesive composition (one-component adhesive)

[0057] As described above, the solid content of the binder composition may be limited to a specific range of 3 to 10 wt % or 4 to 10 wt % based on the total solid content (100 wt %) in the anode mixture including HASE and the AAM / AA / AN copolymer. In this case, the solid content range of the binder composition may be adjusted while physically mixing after measurement, so that the content of HASE may be 0.5 to 50 wt %, and the content of the AAM / AA / AN copolymer may account for the remainder of the total amount (100 wt %) of the binder composition.

[0058] Even if both HASE and AAM / AA / AN copolymer are included, when the content thereof is less than 3 wt % based on the total solid content (100 wt %) in the anode mixture of the binder composition containing the same, the effect thereof is not significant. On the contrary, when the content exceeds 10 wt %, the content of the anode active material may be considerably reduced, thereby reducing the capacity and efficiency of the secondary battery.

[0059] Thus, when the content of the binder composition satisfies 3 to 10 wt % based on the total solid content (100 wt %) in the anode mixture, more preferably when the content satisfies 4 to 10 wt %, excellent properties will be achieved.

[0060] In this case, the "solid content in the anode mixture" may include the anode active material and the binder composition, and may further include solid materials such as a conductive material and the like when added, excluding any solvent added to form a slurry.

[0061] Hydrophobically modified alkali soluble emulsion (HASE)

[0062] The HASE may be a dispersion in which an acrylic polymer having an acid functional group is dispersed in water. In an acidic atmosphere of pH 5 or less, polymer chains may aggregate to have a rigid coiled structure, but in an alkaline atmosphere of pH 7 or more, the polymer chains may unfold and swell. In this case, the acrylic polymer having an acid functional group may be poly(meth)acrylic acid, etc., but is not limited thereto.

[0063] In the present disclosure, an alkali-soluble emulsion can be used, which is modified to have a hydrophobic functional group by copolymerizing a monomer having a hydrophobic functional group in an alkali-soluble emulsion as described above. In this case, the hydrophobic functional group can be an aliphatic hydrocarbon having a long chain, such as an alkyl group having 5 to 20 carbon atoms.

[0064] Specifically, the hydrophobically modified alkali-soluble emulsion can be an emulsion in which an acrylic polymer containing a hydrophobic functional group and an acid functional group is dispersed in water, and more specifically, it can be an emulsion in which an acrylic polymer bonded to a polymer electrolyte main chain having an acid functional group through a hydrophobic side functional group is dispersed in water to form a latex form.

[0065] As a more specific example, the acrylic polymer containing a hydrophobic functional group and an acid functional group may be a copolymer comprising a repeating unit represented by the following Chemical Formula 1 and a repeating unit represented by the following Chemical Formula 2, wherein the repeating unit represented by the following Chemical Formula 1 is a hydrophobic functional group and the repeating unit represented by the following Chemical Formula 2 is an acid functional group:

[0066] [Chemical formula 1]

[0067]

[0068] [Chemical formula 2]

[0069]

[0070] In Chemical Formula 1, n is an integer of 1 to 10.

[0071] As HASE, a commercially available product can be purchased and used, for example, ASE, HASE, HEUR, etc. from BASF can be used.

[0072] The HASE may have a weight average molecular weight of 50,000 to 200,000 g / mol. For example, the weight average molecular weight of the HASE may be 50,000 g / mol or more, 70,000 g / mol or more, 90,000 g / mol or more, or 100,000 g / mol or more, and 200,000 g / mol or less, 180,000 g / mol or less, 160,000 g / mol or less, or 140,000 g / mol or less. The HASE satisfying the above weight average molecular weight conditions is used in combination with the AAM / AS / AN copolymer in a specific content to optimize the viscosity of the adhesive composition, thereby improving the initial adhesion of the anode, reducing the amount of electrode desorption when the anode is cut, reducing the initial resistance of the anode, and providing an anode mixture that can improve the life of the secondary battery.

[0073] As described above, HASE in latex form can have a high viscosity of 300 to 5000 Cp at 20°C, making it useful for increasing the viscosity of aqueous solutions.

[0074] Therefore, when HASE is added to an anode slurry composition, the viscosity can be controlled to improve the stability of the slurry composition.

[0075] In addition, the HASE can be added to the binder composition containing the AAM / AA / AN copolymer in an emulsion state and used to manufacture the anode, and after drying, the HASE can exist in the anode in a solid phase. The solid phase can include a state in which a mixture of the HASE and the AAM / AA / AN copolymer is dispersed.

[0076] The HASE content may be 0.5 to 50 wt % of the total slurry amount, based on the total amount (100 wt %) of the adhesive composition including the HASE and the AAM / AA / AN copolymer.

[0077] However, as the content of the hydrophobically modified alkali soluble emulsion (HASE) in the binder composition increases, the stability of the electrode slurry increases, but the adhesion of the electrode decreases. As the content decreases, the adhesion of the electrode increases, but the stability of the electrode slurry decreases, resulting in a phase change.

[0078] Considering this trend, the content of the hydrophobically modified alkali-soluble emulsion (HASE) may be 0.5 wt % or more, 5 wt % or more, 15 wt % or more, or 25 wt % or more, and 50 wt % or less, 45 wt % or less, 40 wt % or less, or 35 wt % or less, based on the total amount (100 wt %) of the adhesive composition. Meanwhile, the AAM / AA / AN copolymer may account for the remainder other than the HASE content, based on the total amount (100 wt %) of the adhesive composition.

[0079] AAM / AA / AN copolymer

[0080] Based on the total amount (100 wt %) of the adhesive composition, the AAM-based first repeating unit can be included in an amount of 35 to 90 wt %, specifically 40 to 85 wt %, for example 50 to 80 wt %; the AA-based second repeating unit can be included in an amount of 0.1 to 30 wt %, specifically 1 to 28 wt %, for example 3 to 25 wt %; and the AN-based third repeating unit can be included in an amount of 5 to 40 wt %, specifically 10 to 35 wt %, for example 15 to 30 wt %.

[0081] Within this range, the properties of each repeating unit can be coordinated to improve the lifespan of the secondary battery.

[0082] In addition, the AAM / AA / AN copolymer may be provided by a polymerization reaction using a monomer including the first to third repeating units and a polymerization initiator.

[0083] In addition, the AAM / AA / AN copolymer may be formed in the form of an adhesive latex having a solid content of 30 to 60 wt % or 40 to 50 wt %. The AAM / AA / AN copolymer may have a weight average molecular weight of 200,000 to 800,000 Mw.

[0084] Anode active material

[0085] The anode active material may be included in an amount of 85 wt % to 95.5 wt % based on the total solid content (100 wt %) in the anode mixture.

[0086] As described above, as the content of the anode active material increases, the secondary battery may have high capacity and high efficiency. However, as the content of the anode active material increases, there may be a problem that the content of the binder composition needs to be relatively reduced.

[0087] Taking this tendency into consideration, the content of the binder composition may be adjusted, and thus the content of the anode active material may be determined.

[0088] The anode active material may include a material capable of reversibly intercalating and deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of being doped into and dedoped from lithium, or a transition metal oxide.

[0089] The material capable of reversibly embedding and de-embedding lithium ions can be a carbon material, wherein any carbon-based anode active material commonly used for lithium ion secondary batteries can also be used herein, and its representative examples may include crystalline carbon, amorphous carbon or a combination thereof. The example of crystalline carbon may include graphite, such as amorphous, plate-like, thin-sheet, spherical or fibrous natural graphite or artificial graphite, and the example of amorphous carbon may include soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide, calcined coke, etc.

[0090] The alloy of lithium metal used in this article can be an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, or Sn.

[0091] The material that can be doped into lithium and de-doped from lithium can be Si, SiO x (0 < x < 2), Si-C composite material, Si-Q alloy (where Q is an alkali metal, alkaline earth metal, Group 13 to 16 element, transition metal, rare earth element, or a combination thereof, but not Si), Sn, SnO2, Sn-C composite material, Sn-R (where R is an alkali metal, alkaline earth metal, Group 13 to 16 element, transition metal, rare earth element, or a combination thereof, and not Sn), etc. Specific elements of Q and R can include Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof.

[0092] The transition metal oxide can be vanadium oxide, lithium vanadium oxide, etc.

[0093] For example, the anode active material can include a carbon-based anode active material, which is artificial graphite, natural graphite, soft carbon, hard carbon, or a combination thereof.

[0094] Conductive Materials

[0095] Meanwhile, the anode mixture can further include a conductive material. The conductive material can be used to endow the electrode with conductivity, and any material can be used in the configured battery as long as it is an electron-conductive material that does not cause any chemical changes. Examples of the conductive material used in this article can include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.; metal-based materials, for example, metal powders such as copper, nickel, aluminum, silver, etc., or metal-based materials such as metal fibers; conductive polymers such as polyphenylene derivatives, etc.; or a mixture thereof.

[0096] For example, the conductive material can include at least one selected from the group of carbon-based conductive materials including acetylene black, carbon black, Ketjen black, carbon fiber, or a mixture thereof.

[0097] Based on the total solid content (100% by weight) in the anode mixture, the conductive material can be included in an amount of 0.5% to 3% by weight.

[0098] Method for preparing anode mixture for secondary battery

[0099] In another embodiment of the present disclosure, a method for preparing an anode mixture for a secondary battery may be provided, comprising the steps of: preparing a copolymer by polymerizing an acrylamide (AAM)-based first monomer, an acrylic acid (AA)-based second monomer, and an acrylonitrile (AN)-based third monomer; preparing a binder composition by mixing the copolymer with a hydrophobically modified alkali-soluble emulsion (HASE); and obtaining an anode mixture by mixing the binder composition with an anode active material.

[0100] However, when the binder composition is mixed with the anode active material, the content of the binder composition may be controlled to be 3 to 10 wt % based on the total solid content (100 wt %) in the anode mixture.

[0101] The preparation method may correspond to a method of obtaining an anode mixture having the above-mentioned excellent properties by a simple process of preparing an AAM / AA / AN copolymer, mixing it with HASE at the above-mentioned ratio to prepare a binder composition (one-component binder), and mixing the binder composition with an anode active material.

[0102] Below, descriptions repeated with the above contents are omitted, and each process thereof will be described in detail.

[0103] Process for preparing AAM / AA / AN copolymers

[0104] When preparing the AAM / AA / AN copolymer, emulsion polymerization may be employed.

[0105] Specifically, a monomer mixture may be prepared considering the composition of the AAM / AA / AN copolymer, and the monomer mixture may be emulsion-polymerized in the presence of an emulsifier and a polymerization initiator, thereby obtaining the AAM / AA / AN copolymer composition in the form of a latex.

[0106] More specifically, a monomer mixture including 35 to 90 wt % of the first monomer, 0.1 to 30 wt % of the second monomer, and 5 to 40 wt % of the third monomer may be emulsion polymerized in the presence of an emulsifier and a polymerization initiator.

[0107] The description of the content of each monomer in the monomer mixture may be the same as the description of the content of each repeating unit in the AAM / AA / AN copolymer.

[0108] Emulsion polymerization can be performed by single-stage polymerization or multi-stage polymerization. In this case, single-stage polymerization may refer to a method in which the monomers used herein are put into a single reactor and polymerized simultaneously, and multi-stage polymerization may refer to a method in which the monomers used herein are sequentially polymerized in two or more stages.

[0109] Emulsion polymerization can be carried out in a solution containing an aqueous solvent in the presence of an emulsifier and a polymerization initiator.

[0110] The polymerization temperature and polymerization time of the emulsion polymerization may be appropriately determined. For example, the polymerization temperature may be about 50° C. to about 200° C., and the polymerization time may be about 0.5 hour to about 20 hours.

[0111] As the polymerization initiator available in the emulsion polymerization process, inorganic or organic peroxides can be used. For example, water-soluble initiators including potassium persulfate, sodium persulfate, ammonium persulfate, etc., and oil-soluble initiators including cumene hydroperoxide, benzoyl peroxide, etc. can be used.

[0112] In addition, an activator may be further included together with the polymerization initiator to promote the reaction initiation of the peroxide, and the activator used herein may be at least one selected from sodium formaldehyde sulfoxylate, sodium ethylenediaminetetraacetate, ferrous sulfate, and glucose.

[0113] And, the emulsifier used for emulsion polymerization used in this article can be an anionic emulsifier, such as sodium dodecyl diphenyl oxide disulfonate, sodium lauryl sulfate, sodium dodecylbenzene sulfonate, sodium dioctyl sulfosuccinate, etc., or a nonionic emulsifier, such as polyethylene oxide alkyl ether (such as polyethylene oxide lauryl ether), polyethylene oxide alkyl aryl ether, polyethylene oxide alkyl amine, polyethylene oxide alkyl ester, etc. The above-mentioned emulsifier can be a material having both a hydrophilic group and a hydrophobic group, and in the emulsion polymerization process, a micellar structure can be formed and the polymerization of various monomers can occur inside the micellar structure. Preferably, anionic emulsifiers and nonionic emulsifiers can be used alone, or two or more types thereof are used in combination, and the use of a mixture of anionic emulsifiers and nonionic emulsifiers may be more effective, but the present disclosure is not necessarily limited to such emulsifier types.

[0114] And, the emulsifier may be used in an amount of about 0.01 to about 10 parts by weight, about 1 to about 10 parts by weight, or about 3 to about 5 parts by weight, based on 100 parts by weight of all monomer components used in the preparation of the copolymer.

[0115] Process of mixing AAM / AA / AN copolymer and HASE (process of preparing adhesive composition)

[0116] When the adhesive composition is prepared by mixing the AAM / AA / AN copolymer with HASE, the hydrophobically modified alkali-soluble emulsion (HASE) may be included in an amount of 0.5 to 50 wt % based on the total amount (100 wt %) of the adhesive composition.

[0117] The description of the content of HASE in the adhesive composition may be the same as described above.

[0118] The method of mixing the AAM / AA / AN copolymer and HASE may not be particularly limited.

[0119] Process of mixing a binder composition and an anode active material (process of preparing an anode mixture)

[0120] When the binder composition and the anode active material are mixed, excellent properties of the anode mixture can be achieved only when the content of the binder composition is controlled to be 3 to 10 wt %, and the description thereof may be the same as above.

[0121] The method of mixing the binder composition and the anode active material may not be particularly limited.

[0122] For example, a binderless slurry including an anode active material and a solvent may be prepared, a conductive material may then be optionally added to the binderless slurry, and the binderless slurry and the binder composition may be mixed to prepare the anode mixture slurry.

[0123] Anode and secondary battery

[0124] According to another embodiment of the present disclosure, there is provided an anode for a secondary battery, including: an anode current collector; and an anode mixture layer located on one or both sides of the anode current collector and including the anode mixture.

[0125] According to another embodiment of the present disclosure, there is provided an anode for a secondary battery, comprising: an anode active material; and

[0126] A binder comprising a polymer from a hydrophobically modified alkali-soluble emulsion (HASE); and a copolymer comprising a first repeating unit from an acrylamide (AAM)-based first monomer, a second repeating unit from an acrylic acid (AA)-based second monomer, and a third repeating unit from an acrylonitrile (AN)-based third monomer, wherein the weight ratio between the polymer from the hydrophobically modified alkali-soluble emulsion (HASE) and the copolymer is 1:1 to 10. In this case, the above-mentioned anode current collector may be further included. In addition, the anode current collector and the anode active material may be the same as described below.

[0127] The polymer from the hydrophobically modified alkali-soluble emulsion may include an acrylic polymer including a repeating unit represented by the following Chemical Formula 1 and a repeating unit represented by the following Chemical Formula 2, and may be present in the anode in a dry solid phase after a final drying process:

[0128] [Chemical formula 1]

[0129]

[0130] [Chemical formula 2]

[0131]

[0132] In Chemical Formula 1, n is an integer of 1 to 10.

[0133] Additionally, the acrylic polymer from HASE may have a weight average molecular weight of 50,000 to 200,000 g / mole.

[0134] The weight ratio between the polymer from the hydrophobically modified alkali soluble emulsion (HASE) and the AAM / AA / AN copolymer may be 1:1 to 10, 1:1.5 to 5, or 1:2 to 4. Here, when the weight ratio is 1:1 or less, there may be a problem of reduced electrode adhesion, and when the weight ratio is 1:10 or more, there may be a problem of dispersibility of the anode slurry.

[0135] According to another embodiment of the present disclosure, a secondary battery including the above anode is provided. The secondary battery specifically includes a cathode; an electrolyte; and an anode.

[0136] An anode mixture including the binder composition in a specific content range can ensure high initial adhesion of the anode, reduce the desorption area when the anode is cut, lower the initial resistance of the anode, and ultimately improve the life of the secondary battery.

[0137] Therefore, an anode mixture including the binder composition in a specific range of contents may replace an anode mixture including SBL and CMC.

[0138] Hereinafter, descriptions overlapping with the above contents will be omitted, and the anode and the secondary battery of this embodiment will be described in detail.

[0139] The secondary battery may be implemented as a lithium secondary battery.

[0140] The lithium secondary battery of this embodiment may further include a separator between the cathode and the anode.

[0141] The lithium secondary battery can be classified into cylindrical, prismatic, coin, pouch, etc. according to the shape adopted, and can be classified into bulk and thin film types according to the size. Since the structure and manufacturing method of these batteries are well known in the art, minimal description will be added.

[0142] The anode includes an anode current collector and an anode active material layer formed on the anode current collector.

[0143] As the anode current collector, one selected from copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, and a combination thereof may be used.

[0144] At the same time, the cathode includes a current collector and a cathode active material layer formed on the current collector. As the cathode active material, a compound that can reversibly insert and extract lithium (lithiated insertion compound) can be used. Specifically, at least one of the composite oxides of lithium and a metal selected from cobalt, manganese, nickel and a combination thereof can be used. As a more specific example, a compound represented by any one of the following structural formulas can be used.

[0145] Li a A 1-b X b D2(0.90≤a≤1.8, 0≤b≤0.5); Li a A 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); LiE 1-b X b O 2-c D c (0≤b≤0.5, 0≤c≤0.05); LiE 2-b X b O 4-c D c (0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b X c D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b- c Co b XOtM 2-α T α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Co b X c O 2-α T2(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b X c D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Mn b X c O2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05\0<α<2);Li a Nor 1-b-c Mn b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);Li a Nor b E c G d O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0.001≤d≤0.1);Li a Nor b Co c Mn d GeO2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0.001≤e≤0.1);Li a NiG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a CoG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a MnG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn2G b O4(0.90≤a≤1.8,0.001≤b≤0.1);Li a MnG b PO4(0.90≤a≤1.8,0.001≤b≤0.1);QO2;QS2;LiQS2;V2O5;LiV2O5;LiZO2;LiNiVO4;Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2);LiFePO4。

[0146] In the above structural formula, A is selected from Ni, Co, Mn and combinations thereof; X is selected from Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements and combinations thereof; D is selected from O, F, S, P and combinations thereof; E is selected from Co, Mn and combinations thereof; T is selected from F, S, P and combinations thereof; G is selected from Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V and combinations thereof; Q is selected from Ti, Mo, Mn and combinations thereof; Z is selected from Cr, V, Fe, Sc, Y and combinations thereof; and J is selected from V, Cr, Mn, Co, Ni, Cu and combinations thereof.

[0147] Of course, the compounds listed above can include an anode mixture layer on its surface and can be used after mixing with a compound with an anode mixture layer. The anode mixture layer can include at least one coating element compound selected from oxides, hydroxides, oxyhydroxides, oxycarbonates and hydroxycarbonates of the coating element. The compound used for the anode mixture layer can be amorphous or crystalline. The coating element used for the coating can suitably include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a mixture thereof. The anode mixture layer can be formed by any method (such as spraying or impregnation) that does not adversely affect the physical properties of the cathode active material, as long as the compound uses the above-mentioned coating element. Those skilled in the art can understand the coating method well, and thus will omit its detailed description.

[0148] The cathode active material layer also includes a cathode binder and a conductive material.

[0149] The cathode binder may be used to allow cathode active material particles to adhere well to each other and also to adhere the cathode active material to a current collector.

[0150] Representative examples of the cathode binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resins, and nylon, but the present disclosure is not limited thereto.

[0151] The conductive material is used to impart conductivity to the electrode, and any conductive material that does not cause chemical changes in the battery can be used. Examples of the conductive material may include natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, metal powders such as copper powder, nickel powder, aluminum powder and silver powder, metal fibers, etc., and conductive materials such as polyphenylene derivatives may be used alone or in combination.

[0152] In addition, Al may be used as a current collector, but is not limited thereto.

[0153] The anode and cathode can be prepared by mixing the active material, the conductive material and the binder in a solvent to prepare an active material slurry, and applying the composition to a current collector. Since such electrode manufacturing methods are well known in the art, detailed descriptions thereof will be omitted here. The solvent may include, but is not limited to, N-methylpyrrolidone.

[0154] Meanwhile, the lithium secondary battery may be a nonaqueous electrolyte secondary battery, and in this case, the nonaqueous electrolyte may include a nonaqueous organic solvent and a lithium salt.

[0155] The nonaqueous organic solvent serves as a medium through which ions participating in the electrochemical reaction of the battery can move.

[0156] In addition, as described above, a separator may be present between the cathode and the anode. As the separator, polyethylene, polypropylene, polyvinylidene fluoride or a multilayer film of two or more layers thereof may be used. Mixed multilayer films such as polyethylene / polypropylene double-layer separators, polyethylene / polypropylene / polyethylene three-layer separators and polypropylene / polyethylene / polypropylene three-layer separators may be used.

[0157] Hereinafter, the present invention will be described in detail with reference to the following examples. However, such examples are provided only for better understanding of the present invention, and therefore the scope of the present invention is not limited thereto.

[0158] HASE (Hydrophobic modified alkali soluble emulsion)

[0159] As hydrophobically modified alkali swellable emulsion (HASE), ACRYSOL TT-935 from ROHM and HAAS was used.

[0160] Its weight average molecular weight is about 120,000 g / mole.

[0161] Preparation Example 1: AAM (70 parts by weight) / AA (5 parts by weight) / AN (25 parts by weight) copolymer

[0162] 250 parts by weight of distilled water, 70 parts by weight of acrylamide, 5 parts by weight of acrylic acid and 25 parts by weight of acrylonitrile were added to a pressure stirrer, followed by 0.4 parts by weight of sodium lauryl sulfate as an emulsifier and 0.5 parts by weight of potassium persulfate as a polymerization initiator to initiate a reaction. Subsequently, the reaction was carried out for 10 hours while being sufficiently stirred and maintained at 70° C. to obtain an adhesive latex having a solid content of 40%.

[0163] Preparation Example 2: AAM (60 parts by weight) / AA (20 parts by weight) / AN (20 parts by weight) copolymer

[0164] 250 parts by weight of distilled water, 60 parts by weight of acrylamide, 20 parts by weight of acrylic acid and 20 parts by weight of acrylonitrile were added to a pressure stirrer, followed by 0.4 parts by weight of sodium lauryl sulfate as an emulsifier and 0.5 parts by weight of potassium persulfate as a polymerization initiator to initiate a reaction. Subsequently, the reaction was carried out for 10 hours while being sufficiently stirred and maintained at 70° C. to obtain an adhesive latex having a solid content of 40%.

[0165] Preparation Example 3: Preparation of One-Component Adhesive A

[0166] 0.3 parts by weight of HASE and 0.7 parts by weight of the AAM / AA / AN copolymer of Preparation Example 1 were mixed at room temperature to obtain a one-component adhesive A.

[0167] Preparation Example 4: Preparation of One-Component Adhesive B

[0168] 0.3 parts by weight of HASE and 0.7 parts by weight of the AAM / AA / AN copolymer of Preparation Example 2 were mixed at room temperature to obtain a one-component adhesive B.

[0169] Comparative Example 1: Anode mixture including 1.0 wt% of one-component binder A

[0170] (1) Preparation of anode mixture slurry

[0171] First, 5 parts by weight (20% by weight solid content) of the one-component adhesive A of Preparation Example 3 and 1 part by weight of a conductive material (SuperC65) are added to 50 parts by weight of deionized water as a solvent, while stirring with a homodisper to prepare a solution, thereby preparing a dispersion in which the contents are dispersed.

[0172] An anode slurry composition was prepared by mixing 98 parts by weight of an anode active material (natural graphite) in the dispersion using an anode mixer to prepare a slurry, and adding 50 parts by weight of deionized water to the slurry as a diluent to adjust the viscosity of the slurry to about 5,000 cP.

[0173] Therefore, 1.0 wt% of the one-component binder A was included based on 100 wt% of the total solid content of the anode mixture slurry of Comparative Example 1.

[0174] (2) Preparation of anode

[0175] A copper foil with a thickness of 20 μm was prepared and used as the anode current collector. A comma coater was used to coat the anode current collector with 4.0 mg / cm2 of copper foil on each side. 2The anode mixture slurry of Comparative Example 1 was applied in an amount of 100 Å, dried with hot air in an oven at 80° C. for 10 minutes, and roll-pressed to form an anode mixture layer.

[0176] Thus, an anode of Comparative Example 1 (total thickness: 80 μm) was obtained.

[0177] (3) Preparation of secondary batteries

[0178] 90 parts by weight of Li as the cathode active material was used. 1.03 Ni 0.6 Co 0.6 Mn 0.2 O2, 5 parts by weight of acetylene black as a conductive material and 50 parts by weight (10% solid) of polyvinylidene fluoride (PVdF) as a binder were mixed in NMP as a solvent while stirring for one hour. Here, the slurry phase was adjusted so that the total solid content was 70% by weight to obtain the cathode mixture of Comparative Example 1.

[0179] Aluminum foil with a thickness of 20 μm was prepared and used as a cathode current collector. A comma coater was used to coat both sides of the cathode current collector at a temperature of 15.6 mg / cm2 per side of the cathode current collector. 2 The cathode mixture of Comparative Example 1 was applied in an amount of 100 Å, dried with hot air in an oven at 80° C. for 10 minutes, and rolled to a total thickness of 190 μm. Thus, the cathode of Comparative Example 1 was obtained.

[0180] A separator was interposed between the anode and cathode of Comparative Example 1 and assembled, followed by injection of an electrolyte to complete a lithium ion battery according to a method conventionally known in the art.

[0181] As an electrolyte, LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) (weight ratio of EC:PC:DEC = 3:2:5) to reach a concentration of 1.3 M, and fluoroethylene carbonate (FEC) was added to account for 10 wt % of the total weight of the electrolyte.

[0182] Example 1: Anode mixture including 3.0 wt% of one-component binder A

[0183] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 1, except that the content of the one-component binder A of Preparation Example 3 was changed to 3.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0184] Specifically, in Example 1, 3 parts by weight of the one-component adhesive A was added to 97 parts by weight of the adhesive-free slurry.

[0185] Example 2: Anode mixture including 4.0 wt% of one-component binder A

[0186] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 1, except that the content of the one-component binder A of Preparation Example 3 was changed to 4.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0187] Specifically, in Example 2, 4 parts by weight of the one-component adhesive A was added to 96 parts by weight of the adhesive-free slurry.

[0188] Example 3: Anode mixture including 5.0 wt% of one-component binder A

[0189] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 1, except that the content of the one-component binder A of Preparation Example 3 was changed to 5.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0190] Specifically, in Example 3, 5 parts by weight of the one-component adhesive A was added to 95 parts by weight of the binder-free slurry.

[0191] Example 4: Anode mixture including 7.0 wt% of one-component binder A

[0192] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 1, except that the content of the one-component binder A of Preparation Example 3 was changed to 7.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0193] Specifically, in Example 4, 7 parts by weight of the one-component adhesive A was added to 93 parts by weight of the binder-free slurry.

[0194] Example 5: Anode mixture including 10.0 wt% of one-component binder A

[0195] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 1, except that the content of the one-component binder A of Preparation Example 3 was changed to 10.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0196] Specifically, in Example 5, 10 parts by weight of the one-component adhesive A was added to 90 parts by weight of the binder-free slurry.

[0197] Comparative Example 2: Anode mixture including 1.0 wt% of one-component binder B

[0198] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 1, except that the one-component binder B of Preparation Example 4 was used instead of the one-component binder A.

[0199] Example 6: Anode mixture including 3.0 wt% of one-component binder A

[0200] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 2, except that the content of the one-component binder B of Preparation Example 4 was changed to 3.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0201] Specifically, in Comparative Example 4, 3 parts by weight of the one-component adhesive B was added to 97 parts by weight of the adhesive-free slurry.

[0202] Example 7: Anode mixture including 4.0 wt% of one-component binder A

[0203] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 2, except that the content of the one-component binder B of Preparation Example 4 was changed to 4.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0204] Specifically, in Example 7, 4 parts by weight of the one-component adhesive B was added to 96 parts by weight of the binder-free slurry.

[0205] Example 8: Anode mixture including 5.0 wt% of one-component binder B

[0206] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 2, except that the content of the one-component binder B of Preparation Example 4 was changed to 5.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0207] Specifically, in Example 8, 5 parts by weight of the one-component adhesive B was added to 95 parts by weight of the binder-free slurry.

[0208] Example 9: Anode mixture including 7.0 wt% of one-component binder B

[0209] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 2, except that the content of the one-component binder B of Preparation Example 4 was changed to 7.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0210] Specifically, in Example 9, 7 parts by weight of the one-component adhesive B was added to 93 parts by weight of the binder-free slurry.

[0211] Example 10: Anode mixture including 10.0 wt% of one-component binder B

[0212] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 2, except that the content of the one-component binder B of Preparation Example 4 was changed to 10.0 wt % based on 100 wt % of the total solid content of the anode mixture slurry.

[0213] Specifically, in Example 10, 10 parts by weight of the one-component adhesive B was added to 90 parts by weight of the binder-free slurry.

[0214] Comparative Example 3: Anode mixture including 1 wt% of binder SBL and 1.0 wt% of CMC

[0215] (1) Adhesive (SB latex)

[0216] 250 parts by weight of distilled water, 50 parts by weight of 1,3-butadiene, 34 parts by weight of styrene, 10 parts by weight of methyl methacrylate, 4 parts by weight of acrylic acid and 2 parts by weight of sodium acrylate were added to a pressure stirrer, followed by 0.4 parts by weight of sodium lauryl sulfate as an emulsifier and 0.5 parts by weight of potassium persulfate as a polymerization initiator to initiate a reaction. Subsequently, the reaction was carried out for 10 hours while being sufficiently stirred and maintained at 70° C. to obtain a SBL adhesive A latex having a solid content of 40%.

[0217] (2) Preparation of anode mixture slurry

[0218] 100 parts by weight of a CMC aqueous solution in which 1% by weight of CMC was dissolved as a dispersant and 1 part by weight of a conductive material (SuperC65) were added and stirred for 0.2 hours to prepare a conductive material dispersion.

[0219] To 101 parts by weight of the above conductive material dispersion, 98 parts by weight of artificial graphite (D50: 15 micrometers) as an anode active material and 50 parts by weight of distilled water as a solvent were added and stirred for 0.8 hours to prepare a binderless slurry.

[0220] To 250 parts by weight of the above binder-free slurry, 2.5 parts by weight of SBL binder A latex was added and stirred for 20 minutes to obtain an anode mixture slurry of Comparative Example 3.

[0221] Therefore, based on 100 wt % of the total solid content of the anode mixture slurry of Comparative Example 3, 1.0 wt % of SBL and 1.0 wt % of CMC were included.

[0222] (3) Preparation of anode and secondary battery

[0223] An anode and a secondary battery were prepared in the same manner as in Comparative Example 1, except that the anode mixture slurry of Comparative Example 3 was used instead of the anode mixture slurry of Comparative Example 1.

[0224] Comparative Example 4: Anode mixture comprising 3 wt% of binder SBL and 1.0 wt% of CMC

[0225] (1) Adhesive

[0226] SBL Adhesive A latex was prepared in the same manner as in Comparative Example 3 and used.

[0227] (2) Preparation of anode mixture slurry

[0228] 100 parts by weight of a CMC aqueous solution in which 1% by weight of CMC was dissolved as a dispersant and 1 part by weight of a conductive material (SuperC65) were added and stirred for 0.2 hours to prepare a conductive material dispersion.

[0229] To 101 parts by weight of the above conductive material dispersion, 98 parts by weight of artificial graphite (D50: 15 micrometers) as an anode active material and 50 parts by weight of distilled water as a solvent were added and stirred for 0.8 hours to prepare a binderless slurry.

[0230] To 245 parts by weight of the above binder-free slurry, 7.5 parts by weight of SBL binder A latex was added and stirred for 20 minutes to obtain an anode mixture slurry of Comparative Example 4.

[0231] Therefore, based on 100 wt % of the total solid content of the anode mixture slurry of Comparative Example 4, 3.0 wt % of SBL and 1.0 wt % of CMC were included.

[0232] (3) Preparation of anode and secondary battery

[0233] An anode and a secondary battery were prepared in the same manner as in Comparative Example 1, except that the anode mixture slurry of Comparative Example 4 was used instead of the anode mixture slurry of Comparative Example 1.

[0234] Comparative Example 5: Anode mixture including 4.0 wt% of one-component binder C

[0235] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Example 7, except that the single-component binder C was used instead of the single-component binder A.

[0236] Specifically, 1 part by weight of HASE and 3 parts by weight of PAAM (weight average molecular weight: Aladdin, Mw=2,000,000) were mixed at room temperature to obtain a one-component adhesive C.

[0237] Comparative Example 6: Anode mixture including 4.0 wt% of one-component binder D

[0238] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Example 7, except that the one-component binder D was used instead of the one-component binder A.

[0239] Specifically, 1 part by weight of HASE and 3 parts by weight of PAA (weight average molecular weight: Aladdin, Mw=1,250,000) were mixed at room temperature to obtain a one-component adhesive D.

[0240] Comparative Example 7: Anode mixture including 4.0 wt% of one-component binder E

[0241] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Example 7, except that the one-component binder E was used instead of the one-component binder A.

[0242] Specifically, 1 part by weight of HASE and 3 parts by weight of PAN (weight average molecular weight: Aladdin, Mw=150,000) were mixed at room temperature to obtain a one-component adhesive E.

[0243] Comparative Example 8: Anode mixture including 4.0 wt% of PAAM+PAA mixture

[0244] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Example 7, except that a mixed binder of PAAM and PAA was used instead of the single-component binder A.

[0245] Specifically, a hybrid adhesive of PAAM and PAA was prepared by mixing PAA (Aladdin, Mw=1,250,000) and PAM (Aladdin, Mw=2,000,000) at a weight ratio of 1:1 at room temperature.

[0246] Comparative Example 9: Anode mixture containing 4.0 wt% of VDF / HFP / AA copolymer

[0247] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Example 7, except that a copolymer binder of VDF, HFP, and AA was used instead of the single-component binder A.

[0248] Specifically, to prepare a mixed adhesive of PAAM and PAA, 1295 parts by weight of demineralized water, 0.75 parts by weight of methylcellulose, 4.0 g of propylene peroxide dicarbonate, 467.8 g of vinylidene fluoride (VDF), 24.8 parts by weight of hexafluoropropylene (HFP) and 7.4 parts by weight of acrylic acid (AA) were added to a 1-liter autoclave reactor and suspension polymerization was performed at 28°C for 60 hours. After the polymerization was completed, the suspension was degassed. Subsequently, the polymer slurry was dehydrated, washed and dehydrated, and then dried in an oven at 80°C for 24 hours to obtain a copolymer.

[0249] The weight average molecular weight of the obtained copolymer was 1,120,000 g / mol.

[0250] Comparative Example 10: Anode mixture including 20.0 wt% of one-component binder A

[0251] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 1, except that the content of the one-component binder A was changed to 20.0 wt % based on 100 wt % of the total anode mixture slurry.

[0252] Specifically, in Comparative Example 10, 20 parts by weight of the one-component adhesive A was added to 79 parts by weight of the adhesive-free slurry.

[0253] Comparative Example 11: Anode mixture including 20.0 wt% of one-component binder B

[0254] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 2, except that the content of the one-component binder B was changed to 20.0 wt % based on 100 wt % of the total anode mixture slurry.

[0255] Specifically, in Comparative Example 11, 20 parts by weight of the one-component adhesive B was added to 79 parts by weight of the adhesive-free slurry.

[0256] Comparative Example 12: Anode mixture in which each component is mixed separately instead of a single-component binder

[0257] The anode active material, HASE, the SBL binder A latex of Comparative Example 3, and a conductive material (SuperC65) were mixed together in a weight ratio of 95:1:3:1, and then dissolved in water to prepare an anode slurry.

[0258] Subsequently, an anode and a secondary battery were prepared in the same manner as in Comparative Example 1.

[0259] Comparative Example 13: Anode mixture including 3 wt% of one-component binder F

[0260] An anode mixture slurry, an anode, and a secondary battery were prepared in the same manner as in Comparative Example 1, except that 3 wt % of the one-component binder F was used instead of the one-component binder A based on 100 wt % of the total anode mixture slurry.

[0261] Specifically, 0.6 parts by weight of HASE and 0.4 parts by weight of AAM / AA / AN copolymer were mixed at room temperature to obtain a one-component adhesive F.

[0262] In Comparative Example 13, 3 parts by weight of the one-component adhesive F were added to 96 parts by weight of the binder-free slurry.

[0263] The anode active material content, the type and content of the binder, and the content of CMC based on the total solid content (100 wt %) of each anode mixture slurry of Examples 1 to 10 and Comparative Examples 1 to 13 are summarized in Table 1 below.

[0264] [Table 1]

[0265]

[0266]

[0267] Experimental Example 1: Evaluation of the Stability of Anode Mixture Slurry

[0268] In order to evaluate the stability during storage, the viscosity of each anode mixture slurry prepared in Examples 1 to 6 and Comparative Examples 1 to 9 was measured immediately after preparation, and the viscosity was measured after 24 hours.

[0269] At each time point, the viscosity was measured using a Brookfield viscometer with RV model and spindle #4, and the stable value after 1 minute or more at 10 rpm was taken as the viscosity value. Also, the slurry was stored in a closed planetary mixer while stirring at a low speed of 15 rpm until just before the viscosity measurement.

[0270] Compared with the initial viscosity, the viscosity after 24 hours was calculated as a percentage (viscosity change rate) according to the following Equation 1 and is shown in Table 2 below.

[0271] [Equation 1] Viscosity change rate = 100*(viscosity after 24 hours) / (initial viscosity)

[0272] [Table 2]

[0273] Anode mixture slurry Viscosity change rate Anode mixture slurry Viscosity change rate Comparative Example 1 158% Comparative Example 3 113% Example 1 113% Comparative Example 4 110% Example 2 110% Comparative Example 5 108% Example 3 108% Comparative Example 6 111% Example 4 110% Comparative Example 7 110% Example 5 107% Comparative Example 8 113% Comparative Example 2 163% Comparative Example 9 188% Example 6 118% - -

[0274] Test Example 2: Evaluation of anode and secondary battery

[0275] The anodes and lithium secondary batteries prepared in Examples 1 to 10 and Comparative Examples 1 to 13 were evaluated under the following conditions, respectively, and the results are shown in Table 3 below.

[0276] Initial adhesion of anode: The peel strength was measured 5 times or more immediately after each anode was prepared, and the average value thereof is shown in the following Table 3. In this case, the peel strength was measured using a tensiometer (Stable Micro System, TA-XT) as the force (gf) required to remove the tape having a width of 10 mm from the anode at a peeling angle of 180° after the anode was adhered to the tape.

[0277] Initial resistance of the anode: After preparing a button half-cell using the prepared anode as the cathode, the resistance value was measured using a Toscat 3100 charge and discharge test system from TOYO under a current rate condition of 3 times the capacity of the button half-cell.

[0278] Desorption area when cutting anode: Each anode was cut using an electrode puncher under the condition of 20*1000 mm. As a result, the area of ​​the anode mixture layer desorbed from the anode current collector was measured from the area (100 sq%), and the measured values ​​are shown in Table 3 below.

[0279] Capacity retention rate of secondary battery after 300 cycles: One cycle was set to discharge each lithium secondary battery to 0.005 V in CC / CV mode at 0.2 C in a thermostatic chamber at 25° C., and then charge to 1.5 V in CC mode at 0.2 C with a rest of 20 minutes between charge and discharge. Here, a total of 300 cycles were performed.

[0280] As shown in Equation 2 below, the ratio of the discharge capacity measured at the 300th cycle to the discharge capacity measured at the first cycle was calculated.

[0281] [Equation 2]

[0282] Capacity retention after 300 cycles (%) = 100*(300th charge capacity) / (1st charge capacity)

[0283] [Table 3]

[0284]

[0285]

[0286] According to Table 3 above, it can be understood that, compared with Comparative Examples 1 to 13, Examples 1 to 10 ensure the initial adhesion of the anode and the initial resistance of the anode, have a very narrow desorption area of ​​the anode mixture layer when the anode is cut, and ensure at least 65% and up to 93% of the capacity retention rate of the secondary battery after 300 cycles. In other words, it is found that the anode according to Examples 1 to 10 includes a binder component that satisfies the weight ratio range of about 1:2 to 3 between the polymer from the hydrophobically modified alkali-soluble emulsion (HASE) and the copolymer in the anode, and thereby ensures that the initial adhesion of the anode is higher than that of the comparative example, reduces the desorption area when the anode is cut, reduces the initial resistance of the anode, and shows an excellent capacity retention rate of the secondary battery after 300 cycles due to satisfying at least 65% or more. Therefore, when the anode according to the present disclosure is included, the life of the secondary battery can be ultimately improved.

[0287] Specifically, although a single-component adhesive (single-component adhesive A and B) - a mixture of AAM / AA / AN copolymer and HASE was applied to Comparative Examples 1 and 2, and its content was found to be 1 wt %, respectively, thereby ensuring an adhesion of 3 gf / inch or more, a resistance of 5.0 mΩ or less, and a certain degree of desorption area when the anode was cut just after the anode was prepared, the capacity retention rate of the secondary battery was 60% or less after 300 cycles, which was lower than that of Examples 1 to 10.

[0288] Furthermore, Comparative Examples 3 and 4, in which CMC (sodium carboxymethyl cellulose) as a dispersant and thickener was mixed with styrene butadiene latex (SBL) as a conventional anode binder, ensured adhesion of 3 gf / inch or more and resistance of 5.0 mΩ or less just after the anode was prepared, but showed that the anode was 3 cm thick when the anode was cut. 2 or higher and a capacity retention rate of the secondary battery as low as less than 30% after 300 cycles.

[0289] This means that the anode mixture layer is severely desorbed when the anode is slit due to the brittleness of CMC and the low adhesion of SBL, and the anode adhesion is gradually weakened during the operation of the secondary battery.

[0290] Meanwhile, in Comparative Examples 5 to 7 in which CMC was not used and a mixture of HASE and any one of PAAM, PAA and PAN (single component adhesives C to E) was applied as an adhesive, the test results were improved compared to Comparative Examples 3 and 4. However, the desorption area when the anode was cut was as wide as 0.8 cm 2or higher, and the capacity retention rate of the secondary battery after 300 cycles is as low as less than 80%. In addition, Comparative Examples 5 to 7 show a resistance of 5.0 mΩ or lower, but the initial resistance is higher than that of Examples 1, 2, 6 and 7 with similar solid contents (3 to 4 wt %) using a single-component adhesive A or B, thereby showing an effect lower than that of the above-mentioned Examples.

[0291] In Comparative Example 8, in which a mixture of PAAM and PAA was used as a binder and no thickener (CMC) was used, the test results were improved compared to Comparative Examples 3 and 4. However, the desorption area when the anode was cut was as wide as 1.2 cm 2 or more, and the capacity retention rate of the secondary battery after 300 cycles was as low as less than 80%.

[0292] In Comparative Example 9, in which the VDF-HFP-AA copolymer was applied as a binder and no thickener (CMC) was used, the test results were much worse than those of Comparative Examples 3 and 4.

[0293] Comparative Examples 10 and 11, in which 20% of the one-component adhesives A and B were applied, respectively, ensured an adhesion of 3 gf / inch just after the anode was prepared, a capacity retention rate of the secondary battery of 80% or more after 300 cycles, and a 3 cm 2 or less desorption area when the anode is cut, but shows a resistance of 5.0 mΩ or more.

[0294] In Comparative Example 12, HASE was used, but a one-component binder was not used, and an anode was prepared by using an anode slurry in which each component was mixed at once. In particular, using SBL binder latex as in Comparative Examples 3 and 4, the desorption area when the anode was cut was as wide as 7 cm 2 or more, and the capacity retention rate of the secondary battery was as low as less than 25%. In addition, in Comparative Example 12, the initial adhesion of the anode and the initial resistance of the anode were inferior to those of the Examples.

[0295] In Comparative Example 13, the content ratio of AAM / AA / AN copolymer to HASE was about 1:0.7, wherein the copolymer was relatively small, thereby ensuring an initial adhesion of 3 gf / inch or more just after the anode was prepared, but the desorption area when the anode was cut was as wide as 6 cm 2 or more, and the capacity retention rate of the secondary battery after 300 cycles was as low as less than 20%.

[0296] In contrast, Examples 1 to 10 use a single-component binder (single-component binders A and B) that is a mixture of an AAM / AA / AN copolymer and HASE, and the content of the single-component binder is limited to a specific range of 3 to 10 wt % based on the solid content of the anode mixture slurry (100 wt %).

[0297] Therefore, it was found that Examples 1 to 10 had a 2.0 cm 2 or less, while ensuring an adhesion of 30 gf / inch or more and a resistance of 9.0 mΩ or less just after the anode is prepared, and ensuring a capacity retention rate of 65% or more for the secondary battery after 300 cycles.

[0298] In Examples 1 to 10, it was confirmed that the initial adhesiveness and resistance of the anode, the desorption area when the anode was cut, and the life of the secondary battery varied depending on the polymerization ratio of AAM / AA / AN, the mixing ratio thereof with HASE, and the like.

[0299] Thus, as long as a single-component binder which is a mixture of AAM / AA / AN copolymer and HASE is applied and its content in the anode mixture slurry is limited to a specific range, an anode and a secondary battery with excellent properties can be achieved, and the properties of the anode and the secondary battery can be controlled by adjusting the polymerization ratio of AAM / AA / AN and its mixing ratio with HASE.

Claims

1. An anode mixture for a secondary battery, comprising an anode active material and a binder composition, wherein: The adhesive composition comprises: Hydrophobically modified alkali soluble emulsion (HASE); and A copolymer comprising a first repeating unit derived from an acrylamide (AAM)-based first monomer, a second repeating unit derived from an acrylic acid (AA)-based second monomer, and a third repeating unit derived from an acrylonitrile (AN)-based third monomer, and The solid content of the binder composition is 3 to 10 wt % based on 100 wt % of the total solid content in the anode mixture. wherein the weight ratio between the hydrophobically modified alkali-soluble emulsion (HASE) and the copolymer is 1:2 to 4, Wherein, based on 100 wt % of the total amount of the adhesive composition, the content of the hydrophobically modified alkali-soluble emulsion (HASE) is 0.5 to 50 wt %, Wherein, based on 100 wt % of the total amount of the copolymer, the first repeating unit is included in an amount of 35 to 90 wt %, the second repeating unit is included in an amount of 0.1 to 30 wt %, and the third repeating unit is included in an amount of 5 to 40 wt %.

2. The anode mixture for a secondary battery according to claim 1, in, The hydrophobically modified alkali soluble emulsion (HASE) comprises an acrylic polymer containing hydrophobic functional groups and acid functional groups.

3. The anode mixture for a secondary battery according to claim 2, in, The acrylic polymer containing a hydrophobic functional group and an acid functional group comprises a repeating unit represented by the following Chemical Formula 1 and a repeating unit represented by the following Chemical Formula 2: [Chemical formula 1] [Chemical formula 2] In the Chemical Formula 1, n is an integer of 1 to 10.

4. The anode mixture for a secondary battery according to claim 2, in, The acrylic polymer containing a hydrophobic functional group and an acid functional group has a weight average molecular weight of 50,000 to 200,000 g / mol.

5. The anode mixture for secondary battery according to claim 2, in, The hydrophobically modified alkali soluble emulsion (HASE) comprises water as a dispersion medium.

6. The anode mixture for secondary batteries according to claim 1, in, The hydrophobically modified alkali soluble emulsion (HASE) has a viscosity of 300 to 5000 cP at 20°C.

7. The anode mixture for a secondary battery according to claim 1, in, The anode active material is artificial graphite, natural graphite, soft carbon, hard carbon or a combination thereof.

8. The anode mixture for a secondary battery according to claim 1, Further comprising a conductive material.

9. A method for preparing an anode mixture for a secondary battery, comprising the steps of: preparing a copolymer by polymerizing an acrylamide (AAM)-based first monomer, an acrylic acid (AA)-based second monomer, and an acrylonitrile (AN)-based third monomer; preparing an adhesive composition by mixing the copolymer with a hydrophobically modified alkali soluble emulsion (HASE); and obtaining an anode mixture by mixing the binder composition with an anode active material, When the binder composition is mixed with the anode active material, the solid content of the binder composition is controlled to be 3 to 10 wt % based on 100 wt % of the total solid content in the anode mixture. wherein the weight ratio between the hydrophobically modified alkali-soluble emulsion (HASE) and the copolymer is 1:2 to 4, Wherein, based on 100 wt % of the total amount of the adhesive composition, the content of the hydrophobically modified alkali-soluble emulsion (HASE) is 0.5 to 50 wt %, The amount of the first monomer is 35 to 90% by weight, the amount of the second monomer is 0.1 to 30% by weight, and the amount of the third monomer is 5 to 40% by weight.

10. The method for preparing an anode mixture for a secondary battery according to claim 9, in, Emulsion polymerization is employed in the preparation of the copolymer.

11. An anode for a secondary battery, comprising: Anode current collector; and An anode mixture layer located on one side or both sides of the anode current collector and comprising the anode mixture of claim 1.

12. An anode for a secondary battery, comprising: Anode active material; and An adhesive comprising a polymer from a hydrophobically modified alkali soluble emulsion (HASE); and a copolymer comprising a first repeating unit from an acrylamide (AAM)-based first monomer, a second repeating unit from an acrylic acid (AA)-based second monomer, and a third repeating unit from an acrylonitrile (AN)-based third monomer, wherein the weight ratio between the polymer from the hydrophobically modified alkali soluble emulsion (HASE) and the copolymer is 1:2 to 4, Wherein, based on 100 wt % of the total amount of the adhesive, the content of the hydrophobically modified alkali-soluble emulsion (HASE) is 0.5 to 50 wt %, Wherein, based on 100 wt % of the total amount of the copolymer, the first repeating unit is included in an amount of 35 to 90 wt %, the second repeating unit is included in an amount of 0.1 to 30 wt %, and the third repeating unit is included in an amount of 5 to 40 wt %.

13. The anode for a secondary battery according to claim 12, in, The polymer from the hydrophobically modified alkali soluble emulsion (HASE) comprises an acrylic polymer, which comprises a repeating unit represented by the following Chemical Formula 1 and a repeating unit represented by the following Chemical Formula 2, and is present in the anode in a dry solid state: [Chemical formula 1] [Chemical formula 2] In the Chemical Formula 1, n is an integer of 1 to 10.

14. The anode for a secondary battery according to claim 13, in, The acrylic polymer has a weight average molecular weight of 50,000 to 200,000 g / mol.

15. A secondary battery comprising the anode according to claim 11 or 12; an electrolyte; and a cathode.

Citation Information

Patent Citations

  • Code generator comprising asynchronous counter and synchronous counter, and operating method thereof

    KR1020200138514A

  • Binder aqueous solution for lithium ion battery, paste for lithium ion battery electrode and method for manufacturing same, lithium ion battery electrode, and lithium ion battery

    CN110885650A

  • Cathode slurry composition, and cathode and secondary battery manufactured using same

    CN111433945A

  • Electrochemical cell acrylic water dispersion and aqueous paste and manufacturing method of electrode and battery consisting of the same

    JP2012151108A

  • KR20200074889A